Application of in-seam directional drilling technology for gas drainage with benefits to gas outburst control and greenhouse gas reductions in Daning coal mine, China - Lu, Shouqing; Cheng, Yuanping; Ma, Jinmin; Zhang, Yuebing (Natural hazards (Dordrecht), 2014)
Gas outburst disasters are becoming more serious as the underground coal mines become deeper in China, and a thick zone of deformed coal provides conditions favorable to coal and gas outbursts. The Daning coal mine’s main mining seam is the No. 3 coal seam with coal and gas outburst hazard, which often contains two normal coal sub-layers and one deformed sub-layer. Considering both the geological conditions of the coal seam and applications of the in-seam directional longhole drilling technology, a new schematic diagram of in-seam directional longholes for gas drainage is developed. The two borehole layout models of longwall panel and main entries for gas outburst disasters control have been successfully applied. The gas drainage rates of both models are >70 %, and the residual gas contents are both <8 m 3 /t, which can be considered that the gas outburst disasters were effectively controlled. To better guide gas drainage, gas drainage normal and failure modes have been obtained. Although in-seam directional longhole technology has been successfully applied for regional gas drainage with benefits to gas outburst control, there are also some problems that are detrimental to greenhouse gas reductions in gas drainage and gas utilization. The three main problems are air leakage failure in gas drainage, decreasing gas concentration and a low gas utilization ratio. To address the problems mentioned above, five improvements are suggested.